Introduction to the Special Issue of tCBT: supporting and guiding our supervisors. (14th October 2016) - Milne, Derek; Reiser, Robert
Abstract : Supervision is probably the single most effective method for helping therapists to develop competence, capability and a professional identity (Falender & Shafranske, 2004 ; Callahan et al .2009 ; Watkins & Milne, 2014 ). Supervision is also perceived by supervisees as the main influence on their practice (Lucock et al. 2006 ), and has been recognized by governments as an essential component of mental health services in the 21st century (e.g. Care Quality Commission, 2013 ). Paradoxically, supervisors themselves may receive inadequate support and guidance. This is an unacceptable strategic and moral oversight, one which presumably undermines the fidelity of CBT while increasing burnout: in one survey, 82% of participating supervisors expressed dissatisfaction over their support arrangements (Gabbay et al .1999 ). Recent surveys of CBT supervisors indicate that despite an overall sense of satisfaction with supervision, considerably more can be done to support supervisors in terms of developing improved supervisory and training materials (Reiser & Milne, 2016 ). The phrase 'something does not compute' sums up this paradox succinctly (Watkins, 1997, p. 604).